Diversity, distribution and sources of bacteria in residential kitchens - Gilberto E. Flores; Scott T. Bates; J. Gregory Caporaso; Christian L. Lauber; Jonathan W. Leff; Rob Knight; Noah Fierer (Environmental Microbiology, 2013)
Summary Bacteria readily colonize kitchen surfaces, and the exchange of microbes between humans and the kitchen environment can impact human health. However, we have a limited understanding of the overall diversity of these communities, how they differ across surfaces and sources of bacteria to kitchen surfaces. Here we used high‐throughput sequencing of the 16 S rRNA gene to explore biogeographical patterns of bacteria across > 80 surfaces within the kitchens of each of four households. In total, 34 bacterial and two archaeal phyla were identified, with most sequences belonging to the A ctinobacteria , B acteroidetes , F irmicutes and P roteobacteria . Genera known to contain common food‐borne pathogens were low in abundance but broadly distributed throughout the kitchens, with different taxa exhibiting distinct distribution patterns. The most diverse communities were associated with infrequently cleaned surfaces such as fans above stoves, refrigerator/freezer door seals and floors. In contrast, the least diverse communities were observed in and around sinks, which were dominated by biofilm‐forming G ram‐negative lineages. Community composition was influenced by conditions on individual surfaces, usage patterns and dispersal from source environments. Human skin was the primary source of bacteria across all kitchen surfaces, with contributions from food and faucet water dominating in a few specific locations. This study demonstrates that diverse bacterial communities are widely distributed in residential kitchens and that the composition of these communities is often predictable. These results also illustrate the ease with which human‐ and food‐associated bacteria can be transferred in residential settings to kitchen surfaces.